Trade - why bother? - Hart, Michael (Centre for Trade Policy and Law OttawaCA, 1992)
Provides an overview of Canada's participation in international trade agreements and negotiations. Surveys the federal and provincial policies influencing trade and investment, and outlines the broad range of global economic challenges.